The importance of non-monetary cost in start-up and annual cacao (Theobroma cacao L) production activities in Santander, Colombia - Andrés Zabala; Juan Fuentes; Jorge Castillo; Santiago Roa-Ortiz (Agronomía Colombiana, 2019)
Based on a double-phase methodology (grouping by cluster method and costing) the costs of three activities of cacao establishment and annual management in San Vicente de Chucuri and El Carmen de Chucuri (Santander, Colombia) were structured. The grouping phase identified two productive typologies, one with low technification level and another with a medium level; moreover, technification levels were corroborated through cost structuring, in which, for all the activities, the medium technification typology generated higher average values than the low one. General cost structures showed that the most important item is labor, followed by inputs and plant material. The disaggregation of costs into monetary and non-monetary (implicit cost) showed that producers with low technification and low frequency of input use present 35% of non-monetary costs per tree, while producers with some level of crop management and relatively high execution of activities have a slightly higher non-monetary cost, 45% of the average total cost per tree. Within non-monetary costs, the labor (mainly family labor) contributed, on average, to 34% of the total cost structures, which constitutes a risk management factor when defining the financial equilibrium point of the cacao production activity.